Pengaruh Konten Media Sosial Tiktok Dan Konten Media Sosial Instagram Terhadap Minat Beli Konsumen Genz Di Umkm Kuliner Situbondo - Ulin Nikmah; Dassucik Dassucik; Ahmad Hafas Rasyidi (Universitas Hamzanwadi, 2026)
This study analyzes the influence of TikTok and Instagram social media content on the purchase intention of Generation Z consumers toward culinary MSMEs in Situbondo. The approach used is quantitative with a survey method. The research population is Generation Z who are active TikTok and Instagram users in Situbondo. A sample of 100 respondents was determined through purposive sampling. Data were collected using a Likert scale questionnaire (1–5) and analyzed with multiple linear regression using SPSS. Partial tests show that TikTok content and Instagram content have a positive and significant effect on purchase intention, with TikTok having a greater influence than Instagram. A simultaneous test also demonstrates that the two variables together have a positive and significant effect on purchase intention. A coefficient of determination of 57.4% indicates that variations in purchase intention can be explained by these two variables, while the remainder is influenced by other factors. These findings confirm that integrated use of TikTok and Instagram is an effective digital marketing strategy for culinary MSMEs to increase Generation Z’s purchase intention in Situbondo. This study provides an empirical contribution to the context of culinary MSMEs in non-metropolitan areas that are still relatively under-researched